Reduplikasi Bahasa Melayu Riau Dialek Rokan Hulu di Desa Rantau Kasai Kecamatan Tambusai Utara - Ermawati. S; Yani Saputri (UIR PRESS, 2021)
This research is motivated by the unique reduplication of the Malay language in terms of form and meaning, in terms of form related to the number of syllables produced can be different when translated into Indonesian. Then in terms of meaning, there is a change in meaning if a word undergoes a reduplication process and does not change the meaning of its basic form. The formulation of the problem in this study, namely, (1) What is the form of reduplication of Riau Malay dialect of Rokan Hulu in Rantau Kasai Village, North Tambusai District? and (2) What is the meaning of reduplication of Riau Malay dialect of Rokan Hulu in Rantau Kasai Village, North Tambusai District? The purpose of this study is to describe, analyze and conclude the form and meaning of the Riau Malay language reduplication in the Rokan Hulu dialect in Rantau Kasai Village, North Tambusai District. The method used is ethnography. The data analysis technique used is the Spradley model. The techniques used are interview techniques and note-taking techniques. This research uses Ramlan's opinion. Based on the results of the study, the data used in this study amounted to 119 data. The conclusions in this study are, 1. The form of reduplication contained in Riau Malay dialect of Rokan Hulu in Rantau Kasai Village, North Tambusai District (1). Entire Reduplication (2). Partial Reduplication, (3). Reduplication with the process of affixing affixes, and (4). Phoneme change reduplication. 2. The meaning of reduplication in Riau Malay dialect of Rokan Hulu in Rantau Kasai Village, North Tambusai District (1). Many Meanings, (2). Meaning Repetitive, (3). The meaning of the act with pleasure, (4). Mutual Meaning, (5). Meaning related to work, (6). The highest level of meaning, and (7). The meaning of feeling intensity.